Sphingolipids Modulate Secretion of Glycosylphosphatidylinositol-Anchored Plasmodesmata Proteins and Callose Deposition. Issue 1 (7th July 2020) - Iswanto, Arya Bagus Boedi; Shon, Jong Cheol; Liu, Kwang Hyeon; Vu, Minh Huy; Kumar, Ritesh; Kim, Jae-Yean
Abstract : Arabidopsis glucosyl sphingolipid-modulated plasmodesmal gating involves modulation of the glycosylphosphatidylinositol-anchored PdBG2 protein secretion machinery and a change in callose accumulation. Abstract: Plasma membranes encapsulated in the symplasmic nanochannels of plasmodesmata (PD) contain abundant lipid rafts, which are enriched with sphingolipids (SLs) and sterols. Reduction of sterols has highlighted the role played by lipid raft integrity in the intercellular trafficking of glycosylphosphatidylinositol (GPI)-anchored PD proteins, particularly in affecting callose enhancement. The presence of callose at PD is strongly attributed to the regulation of callose accumulation and callose degradation by callose synthases and β-1, 3-glucanases (BGs), respectively. SLs are implicated in signaling and membrane protein trafficking; however, the underlying processes linking SL composition to the control of symplasmic apertures remain unknown. The wide variety of SLs in plants prompted us to investigate which SL molecules are important for regulating symplasmic apertures in Arabidopsis ( Arabidopsis thaliana ). We introduced several potential SL pathway inhibitors and genetically modified SL contents using two independent SL pathway mutants. We were able to modulate callose deposition to control symplasmic connectivity through perturbations of SL metabolism. Alteration in glucosylhydroxyceramides or related SL composition particularly disturbed the secretory machinery for the GPI-anchored PdBG2 protein, resulting in an overaccumulation of callose. Moreover, our results revealed that SL-enriched lipid rafts link symplasmic channeling to PD callose homeostasis by controlling the targeting of GPI-anchored PdBG2. This study elevates our understanding of the molecular linkage underlying intracellular trafficking and precise targeting of GPI-anchored PD proteins incorporating glucosyl SLs.